Inovasi Produk Pudak “Lakarasa” Sebagai Strategi Pelestarian Kuliner Tradisional Gresik Berbasis Kearifan Lokal - Ragil Putri Ayu Penggalih; Aulia Rahma Safitri; Ruth Larissa Budi Yustina; Tassya Priskilla Sara Leo; Sonja Andarini; Indah Respati Kusumasari (LPPI UMN AL WASHLIYAH, 2025)
Pudak is a traditional culinary product from Gresik that has begun to experience shifting consumer demand trends, especially among younger generations. This study aims to examine the product innovation of Pudak “Lakarasa” as a strategy for preserving traditional cuisine based on local wisdom. The research uses a descriptive qualitative approach through observation, documentation, and interviews with local MSME producers of traditional Gresik souvenirs. The findings show that flavor innovation through the addition of ingredients such as dates successfully increases consumer interest in pudak. This innovation also preserves traditional production techniques, such as the use of ope and bamboo besek packaging, which are integral to local cultural identity. In addition to offering a new, softer, and more balanced taste, the product provides a more visually appealing consumption experience. Although the shelf life of this pudak is shorter due to the absence of preservatives, it becomes an added value in terms of health and product naturalness. Pudak “Lakarasa” not only expands the market segment but also serves as a tangible form of preserving local culinary heritage in Gresik. Future development plans include introducing strawberry and chocolate flavor variants to better align with modern consumer preferences and enhance the product’s competitiveness in both local and national souvenir markets.